PLUTARQUE, DE ISIDE ET OSIRIDE, CHAPITRES 1-11: UN COMMENTAIRE - Nardelli, Jean-Fabrice (Exemplaria Classica, 2015)
Many factors conspire to estrange scholars from the prologue to Plutarch’s treatise On Isis and Osiris. Now that we have G. Roskam’s thorough literary and philosophical study, time has come to bypass the fifty years of beating around the bush that have elapsed since Gwyn Griffiths completed his large-scale edition (1965). Instead, this article offers an in-depth, new detailed commentary on the first eleven chapters, with a full conclusion that gathers its main findings and attempts to show how Plutarch peers through his weird prolegomena and what value attaches to them.